Asian dust storm events are associated with an acute increase in stroke hospitalisation. Issue 2 (23rd July 2012) - Kang, Jiunn-Horng; Liu, Tsai-Ching; Keller, Joseph; Lin, Herng-Ching
Abstract : Objective: Asian dust storms (ADS) are long-ranged meteorological phenomena, which are suggested to be associated with several health problems. This study aimed to investigate the risk of stroke hospitalisation following ADS events by conducting a population-based study. Study design and setting: The authors identified 810 947 hospitalisations with an admission diagnosis of stroke during the time period between 2000 and 2009 in Taiwan. The ARIMA method (Auto-Regressive Integrated Moving Average) was used to examine the associations between ADS episodes and the daily number of stroke hospitalisations. Results: There were 46 separate ADS episodes which resulted in a total of 135 ADS days between 2000 and 2009. The Kruskal–Wallis test revealed that there was a significant difference in the mean number of daily stroke admissions among ADS days (239.6), post-ADS days (249.2) and non-ADS days (219.7) (p<0.001). After adjusting for the time-trend effect, ambient temperature, season, SO2 and CO, the authors found post-ADS days 1 and 2 to have a significantly higher number of stroke admission than non-ADS days. Post-ADS days 1 and 2 had significantly higher numbers of ischaemic but not haemorrhagic stroke admissions. Conclusion: The authors conclude that ADS events are associated with an acute increase in stroke admission rates.